Identification and characterization of a novel small viral peptide (VSP59) encoded by Bombyx mori cypovirus (BmCPV) that negatively regulates viral replication - Manman Cao; Qunnan Qiu; Xing Zhang; Wenxue Zhang; Zeen Shen; Chang Ma; Min Zhu; Jun Pan; Xingyu Tong; Guangli Cao; Chengliang Gong; Xiaolong Hu (Microbiology Spectrum)
ABSTRACT Bombyx mori cypovirus (BmCPV), a member of the Reoviridae family, is a well-established research model for double-stranded RNA (dsRNA) viruses with segmented genomes. Despite its small genome size, the coding potential of BmCPV remains largely unexplored. In this study, we identified a novel small open reading frame within the S10 dsRNA genome, encoding a small viral peptide (VSP59) with 59 amino acid residues. Functional characterization revealed that VSP59 acts as a negative regulator of viral replication. VSP59 predominantly localizes to the cytoplasm, where it interacts with prohibitin 2 (PHB2), an inner membrane mitophagy receptor. This interaction targets mitochondria and triggers caspase 3-dependent apoptosis. Transient expression of vsp59 in BmN cells suppressed viral replication, an effect that was reversed by silencing PHB2 expression. Moreover, recombinant BmCPV with a mutated vsp59 exhibited reduced replication. Our findings demonstrate that VSP59 interacts with PHB2 on mitochondria, inducing apoptosis and thereby diminishing viral replication. This study expands our understanding of the genetic information encoded by the BmCPV genome and highlights the role of novel small peptides in host-virus interactions.IMPORTANCEA novel small open reading frame (sORF) from the viral genome was identified and characterized. The sORF could encode a small viral peptide (VSP59) that targeted mitochondria and induced prohibitin 2-related apoptosis, further attenuating Bombyx mori cypovirus replication.